The content analysis, material presentation, and readability of curriculum 2013 science textbook for 1st semester of junior high school 7th grade - Endik Deni Nugroho; Vlorensius Vlorensius; Laila Rasidah H.; Nur Anisa (University of Muhammadiyah Malang, 2017)
Based on the early observation by researchers of the two Science textbooks 7th Grade about biological material, 1st and 2nd semester of curriculum 2013, there were errors in the material presentation and legibility. This study aimed to compare and find the contents suitability of the book based on standard of competence and basic competences, readability, materials presentation and supporting material in the science textbook VII grade, 1st and 2nd semester and measured student legibility. This study used a qualitative descriptive approach by using document analysis. The data resources were obtained by using purposive, the data collection was triangulation, data analysis was inductive/qualitative and the results emphasized the meaning. This research results showed that the Integrated Sciences and Sciences textbook 1st and 2nd semester meet the standards of the core competencies and basic competence on the syllabus curriculum 2013 and also meet the books standart. The results of the analysis conducted in misstatement concept and principles and material llustration in the Integrated Science textbook 1st semester were found 5 misstatement concept, for the presentation of the principles and material illustration was found no error. In the book Integrated Sciences there was no delivery errors concept, principle, and material illustration. Science textbook 1st semester found 8 concepts misstatements and 8 illustration material misstatements. In general, Integrated Sciences and Sciences textbooks 1st and 2nd semester are illegibility so not appropriate for students.